The Right Of Inquiryof The Representative Council - R. Juli Moertiono (Proceeding International Seminar of Islamic Studies, 2019)
The Legal Aspect of Right of Inquiry ofThe Representative Council and The Process of LaunchingThe Right of Inquiry Normatively, the existence of the right of inquiry s is regulated in Article 20, Clause (2) 1945 Constitution, namely: In implementing its function, The Representative Council has the right of interpellation, the rightof inquiry, and the rightof opinion. Thus, the rightof inquiry which is the right ofThe Representative Councilto investigatetheimperative and strategic governmental policies widely affecting the lives of thepeoplein society and state which is assumed incompatible with the rule of laws. In the other words, the right of inquiry is one right of The Representative Council to control the executive policy. It means that legislative is integral part of another government power, namely executive and judicative power in division system of power according to Montesquieu theory which is known as TriasPolitica. The aim of power division here is to prevent state power to be held only by one hand or body so it is worried that it can cause power misuse by that organ. The shift of power from executive institution to legislative institution in the period after 1945 Constitution amendment, not become the benchmark that legislative power will be bigger and stronger than executive power, and to judicative power. But, the balance is the final aim of governmental and state system. The Representative Council is High Institution of The State which is formally and informallyrepresents Indonesian people in The Government System of The Republic of Indonesia. The Representative Council does the similar duty as mandated in The Constitution as the body which represents peoples interest. The Representative Council as legislative institution in implementing its functions have the rights as regulated and determined in article 19 until article 22B in1945 Constitution amendment.